MODEL KEPEMIMPINAN TRANSFORMASIONAL BERBASIS APRESIASI GURU DALAM MENINGKATKAN MOTIVASI INTRINSIK DAN INOVASI PEMBELAJARAN PADA PENDIDIKAN ANAK - Maya Laelasari; Syadeli Hanafi (STKIP Pesisir Selatan, 2026)
This study aims to examine the implementation of appreciation-based transformational leadership in strengthening teachers’ intrinsic motivation and promoting learning innovation in Early Childhood Education (ECE) institutions. The study focuses on the role of school principals in creating a supportive work environment, recognizing teachers’ contributions, and providing opportunities for professional creativity and participation. This study employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation. The research informants consisted of the school principal and teachers who were purposively selected based on their direct involvement in leadership practices and classroom learning activities. The data were analyzed through data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that low teacher motivation and limited learning innovation are associated with a lack of appreciation, the dominance of administrative-oriented leadership, and limited teacher involvement in school development. The implementation of appreciation-based transformational leadership enhanced teachers’ self-confidence, work engagement, professional collaboration, and willingness to develop more creative learning practices.